Получение структуры и определение механических характеристик монокристаллического фуллерита C60 - Солонин, Ю.М.; Горбань, В.Ф.; Грайворонская, Е.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The structure and mechanical properties of single crystals of fullerite C60 obtained by sublimation of a powder are investigated. The structure is studied by X-ray methods. The mechanical characteristics of the crystals are determined on the basis of microindentation with the use of the diagrams of loading and unloading.